PERBEDAAN KEMAMPUAN BERPIKIR SIMBOLIK ANAK USIA 5-6 TAHUN MELALUI LOOSE PARTS DI TK TUNAS HARAPAN - Bella Agustiara; Dwi Septi Anjas Wulan (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study was to determine the differences in symbolic thinking ability of 5-6 year old children through loose parts at Tunas Harapan Kindergarten. This study used a Quasi Experimental research type with a One Group Pretest-Posttest Design design. The sample in this study amounted to 20 children, the sampling technique used Saturated Sample (Census). The research instrument used was an observation sheet. Statistical analysis in hypothesis testing used the Wilcoxon Signed-rank test. The results of the study showed a significant increase in the pretest results showing a value in the Not Good (TB) category, which was (40%) with an average of 20 and experienced an increase in the posttest results to the Very Good (SB) category of (60%) with an average value of 36. The results of data analysis using the Wilcoxon Signed-rank test showed an Asymp. value. signature. (2 tailed) is 0.000, which means it is smaller than the significance level α = 0.05. Based on the results of the analysis above, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that there is a significant difference in the symbolic thinking ability of children aged 5-6 years through the loose part at Tunas Harapan Kindergarten.